Performance Measurement of PT. Pandu Siwi Sentosa Bukittinggi Branch Uses the Balanced Scorecard Method in 2023 - Nur Faizin; Alizar Hasan (Lembaga Pengembangan Kinerja Dosen, 2026)
This study was motivated by the lack of an optimal comprehensive performance measurement system at PT. Pandu Siwi Sentosa Bukittinggi Branch amid operational challenges such as increased shipping volumes, fluctuations in operating costs, and competition in the logistics industry. The company needs a performance measurement method that not only focuses on financial aspects but also includes customer perspectives, internal business processes, and learning and growth. This study aims to measure the performance of PT. Pandu Siwi Sentosa Bukittinggi Branch in 2023 using the Balanced Scorecard (BSC) approach. This study was conducted using a quantitative descriptive method through questionnaires and secondary data from the company's internal reports. The results show that the company's overall performance is in the “Good” category with a total score of 80.20. The customer perspective achieved the highest score, reflecting a high level of satisfaction and loyalty. Meanwhile, the learning and growth perspective received the lowest score, indicating the need for improvement in employee training, retention, and technology adoption.This study recommends strengthening internal strategies through sustainable human resource development, business process digitization, and performance evaluation system refinement as strategic steps to maintain the company's competitive advantage in the future.